Performance analysis of two dimensional wavelength/ time OCDMA system for optical network - Ahmed Aqrab, Israa Shihab (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The main goal of this research work are to study and investigate the performance of the 2-D W/T MDW code in the 2-D W/T OCDMA network to make improvements in optical channel application ; to investigate the 2-D W/T MDW OCDMA code properties of cross-correlation between users and the ability to cancel MAI at the receiver ; to analyse the performance of 2-D W/T MDW code for different parameters such as the number of users, code sequence length, received power and type of photo-detector, fiber length and different detection techniques.